2019
DOI: 10.1039/c9ra08451g
|View full text |Cite
|
Sign up to set email alerts
|

Optical characteristics of GaAs/GaAsSb/GaAs coaxial single quantum-well nanowires with different Sb components

Abstract: GaAs/GaAs1−xSbx/GaAs coaxial single quantum-well nanowires with larger Sb content result in better electron confinement, which greatly improves their thermal stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…2f shows the PL emission. It is found that with Sb molar fractions increasing from 8 to 12%, the PL emission changes from 1.35 to 1.31 eV (~918 to 947 nm) at 10 K, while the temperature stability improves [76]. The deeper QW is created for higher Sb compositions, which provides more effective confinement for carriers in the quasi-type-II band structure.…”
Section: Qw Structure In Gaas-based Nwsmentioning
confidence: 98%
See 2 more Smart Citations
“…2f shows the PL emission. It is found that with Sb molar fractions increasing from 8 to 12%, the PL emission changes from 1.35 to 1.31 eV (~918 to 947 nm) at 10 K, while the temperature stability improves [76]. The deeper QW is created for higher Sb compositions, which provides more effective confinement for carriers in the quasi-type-II band structure.…”
Section: Qw Structure In Gaas-based Nwsmentioning
confidence: 98%
“…Due to the 1D structure of NWs, QW in NWs can be constructed in two ways, namely, the coreshell structure that forms a QW in the radial direction ( Fig. 1e) [65][66][67][68][69][70][71][72][73][74][75][76][77][78][79], and the dot-in-rod structure that forms a QW in the axial direction ( Fig. 1f) [80][81][82][83][84][85][86][87][88].…”
Section: Gaas-based Qw Nw Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanowires (NWs) with a quasi-one-dimensional structure and large surface-volume ratio have become a good choice for the preparation of various optoelectronic devices, such as solar cells [1,2], lasers [3][4][5][6] and photodetectors [7][8][9][10]. Among them, NW photodetectors have been the focus of research during the past decade [11][12][13].…”
Section: Introductionmentioning
confidence: 99%